High linear energy transfer carbon-ion irradiation upregulates PD-L1 expression more significantly than X-rays in human osteosarcoma U2OS cells. (1st July 2021) - Permata, Tiara Bunga Mayang; Sato, Hiro; Gu, Wenchao; Kakoti, Sangeeta; Uchihara, Yuki; Yoshimatsu, Yukihiko; Sato, Itaru; Kato, Reona; Yamauchi, Motohiro; Suzuki, Keiji; Oike, Takahiro; Tsushima, Yoshito; et al.
Abstract: Programmed death ligand 1 (PD-L1) expression on the surface of cancer cells affects the efficacy of anti-PD-1/PD-L1 immune checkpoint therapy. However, the mechanism underlying PD-L1 expression in cancer cells is not fully understood, particularly after ionizing radiation (IR). Here, we examined the impact of high linear energy transfer (LET) carbon-ion irradiation on the expression of PD-L1 in human osteosarcoma U2OS cells. We found that the upregulation of PD-L1 expression after high LET carbon-ion irradiation was greater than that induced by X-rays at the same physical and relative biological effectiveness (RBE) dose, and that the upregulation of PD-L1 induced by high LET carbon-ion irradiation was predominantly dependent on ataxia telangiectasia and Rad3-related (ATR) kinase activity. Moreover, we showed that the downstream signaling, e.g. STAT1 phosphorylation and IRF1 expression, was upregulated to a greater extent after high LET carbon-ion irradiation than X-rays, and that IRF1 upregulation was also ATR dependent. Finally, to visualize PD-L1 molecules on the cell surface in 3D, we applied immunofluorescence-based super-resolution imaging. The three-dimensional structured illumination microscopy (3D-SIM) analyses revealed substantial increases in the number of presented PD-L1 molecules on the cell surface after high LET carbon-ion irradiation compared with X-ray irradiation.